2016
DOI: 10.3168/jds.2015-10277
|View full text |Cite
|
Sign up to set email alerts
|

Lactose in milk replacer can partly be replaced by glucose, fructose, or glycerol without affecting insulin sensitivity in veal calves

Abstract: Calf milk replacer (MR) contains 40 to 50% lactose. Lactose strongly fluctuates in price and alternatives are desired. Also, problems with glucose homeostasis and insulin sensitivity (i.e., high incidence of hyperglycemia and hyperinsulinemia) have been described for heavy veal calves (body weight >100 kg). Replacement of lactose by other dietary substrates can be economically attractive, and may also positively (or negatively) affect the risk of developing problems with glucose metabolism. An experiment was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 52 publications
5
24
0
Order By: Relevance
“…These problems have been identified in heavy veal calves (4-6 mo), characterized by a high incidence of hyperglycemia, hyperinsulinemia, and glucosuria (Hostettler-Allen et al, 1994;Hugi et al, 1997) and insulin resistance (Pantophlet et al, 2016a). In a recent study, we found that calves raised on a lactose MR diet, or diets in which one-third of the lactose was replaced by glucose, fructose, or glycerol, did not differ in insulin sensitivity and that insulin sensitivity was low (Pantophlet et al, 2016c). This could lead to metabolic disorders and impaired animal growth performance.…”
Section: Short Communicationmentioning
confidence: 87%
See 1 more Smart Citation
“…These problems have been identified in heavy veal calves (4-6 mo), characterized by a high incidence of hyperglycemia, hyperinsulinemia, and glucosuria (Hostettler-Allen et al, 1994;Hugi et al, 1997) and insulin resistance (Pantophlet et al, 2016a). In a recent study, we found that calves raised on a lactose MR diet, or diets in which one-third of the lactose was replaced by glucose, fructose, or glycerol, did not differ in insulin sensitivity and that insulin sensitivity was low (Pantophlet et al, 2016c). This could lead to metabolic disorders and impaired animal growth performance.…”
Section: Short Communicationmentioning
confidence: 87%
“…All calves remained on their diets throughout the trial. A detailed description of the diets and feeding strategy is provided elsewhere (Pantophlet et al, 2016c). In short, calves were fed MR and solid feed (20% wheat straw and 80% concentrates) twice a day, at 0630 and 1530 h. The MR was fed on an individual basis (BW was measured weekly), and solid feed was provided per pen during group housing and per individual calf when the calves were housed in metabolic cages.…”
Section: Short Communication: Supplementation Of Fructo-oligosaccharimentioning
confidence: 99%
“…In agreement, Kesser et al (2017) recently concluded that even though slight changes in insulin sensitivity may be provoked by early life nutrition, these effects are rather transient and they found no evidence for sustained effects. In heavy calves, insulin sensitivity is invariably low, being rather insensitive to the carbohydrate source in the CMR (Pantophlet et al, 2016c) or to an exchange of lactose for fat (euglycemic-hyperinsulinemic clamp; Pantophlet et al, 2016a). Large effects of dietary treatments on postprandial glucose and insulin responses, as often observed (e.g., Vicari et al, 2008a,b), are therefore unlikely to be caused by differences in insulin sensitivity.…”
Section: Glucose Metabolism and Insulin Sensitivitymentioning
confidence: 99%
“…Insulin sensitivity in calves rapidly drops with age. Stanley et al (2002), found 10-to 20-fold higher insulin sensitivities in Holstein and Jersey calves at 4 to 5 wk of age [15 and 25 × 10 −4 (mU/L) −1 × min −1 , respectively], than Pantophlet et al (2016c) in Holstein calves of about 190 kg of BW, both using the frequently sampled intravenous glucose tolerance test (FSIGT). Recent developments in feeding strategies of heifer calves have renewed interest in manipulating insulin sensitivity in early life, based on the promise of improved performance and milk production in later life.…”
Section: Glucose Metabolism and Insulin Sensitivitymentioning
confidence: 99%
“…Persistently high intakes of lactose and fat may lead to dysregulations in glucose homeostasis, which are characterized by a high incidence of hyperglycemia, hyperinsulinemia and glycosuria. These problems have been identified in heavy (4–6 months old) veal calves [13]. In addition, a substantial decrease in insulin sensitivity is observed in calves during the first months of life [4, 5].…”
Section: Introductionmentioning
confidence: 99%